LASER THERAPY IN CHILD NEUROLOGY - D. A. Prityko (Русский журнал детской неврологии)
The current review of studies devoted to efficacy and safety of laser therapy in the treatment of neurological diseases in children is proposed. The author discusses pathophysiological background of this method of therapy, general therapeutic approaches and definite schemes of therapy in different diseases.